Internalisasi Green Halal Lifestyle di SMK NU Bandar untuk Membangun Generasi Islami Peduli Lingkungan - Ariya Puji (JMIMAS: JURNAL PENGABDIAN DAN MITRA MASYARAKAT, 2025)
This community service activity aims to internalize the values of a green halal lifestyle among students of SMK NU Bandar as an effort to build an Islamic generation that is environmentally conscious. The low level of student awareness regarding the importance of a halal lifestyle that aligns with environmental sustainability prompted the service team to implement an integrative educational approach. The methods used included socialization, structured counseling sessions, and participatory discussions targeting three learning domains: cognitive (knowledge), affective (attitude), and psychomotor (behavior). The activity was conducted offline on May 8, 2025, with 31 tenth-grade students participating. The materials were delivered in a systematic and contextual manner, supported by visual aids and real-life examples relevant to the students’ daily experiences. Evaluation results showed a notable improvement in students' understanding after the activity. The average score increased from 71.25 in the pre-test to 89.66 in the post-test. Significant gains, exceeding 30 points, were recorded in areas such as the application of sharia principles in daily life and awareness of school-based environmental campaigns. These results indicate the activity’s effectiveness in enhancing awareness of the intersection between Islamic values and ecological responsibility. This model can be widely replicated to foster Islamic and eco-friendly school environments.